Analisis respon stakeholders terhadap program pemberdayaan masyarakat home industry pengolahan ceker dan bulu ayam di Kelurahan Kampung Mandar Banyuwangi - Alfisyahrin, Rizka Romi; Azizah, Siti; Nugroho, Eko (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2015)
The research was conducted from November 27th to December 30th, 2014 in Kampung Mandar Banyuwangi, East Java. The objectives of the research were to identify the community response to the empowerment program. Thirty respondents were selected as respondents of this program. Primary and secondary data were collected by survey method using a structured questionnaire. Respondents’ responses were analyzed by descriptive analysis. The study found that attitude variable indicated that respondents agreed with the empowerment program and had a desire to continue the program. Perception of the respondents showed that respondents had a high understanding about the topic given in the program and in line to the respondents’ need. With regards to participation variable, the research showed that respondents were active in taking decision to attend the program. Keywords: attitude, perception, participation, empowerment